Jahresbericht : Anno 97-98 Kunstsammlung Nordrhein-Westfalen Düsseldorf. - Breithaupt, Julia; Böhmer, Otmar; Essers, Volkmar; Kruszynski, Anette; Krystof, Doris; Mielke, Brunhilde; Müller, Maria; Müller-Tamm, Pia; Scheit, Stefanie; Spieler, Reinhard; Wenzel, Angela; Zweite, Armin; et al. (Düsseldorf : Kunstsammlung Nordrhein-Westfalen, 1999)
Dali, Salvador ; Darboven, Hanne ; Kelly, Ellsworth ; Lüpertz, Markus ; Schnabel, Julian ; Serra, Richard ; Soutine, Chaim ; Katz, Alex ; Picasso, Pablo ; Warhol, Andy ; Magritte, René ; Newman, Barnett ; Beckmann, Max ; Sieverding, Katharina ; Feininger, Lyonel ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Klee, Paul ; Steinle, Julian Rosefeldt & Piero ; Ernst, Max ; Kirkeby, Per ; Zangs, Herbert
Biografie
Duits
boek